HUBUNGAN PENGETAHUAN DENGAN SIKAP PEMILIHAN KOSMETIKA PERAWATAN KULIT WAJAH MAHASISWA JURUSAN TATA RIAS DAN KECANTIKAN UNIVERSITAS NEGERI PADANG - Q.H, ASSHARA QEMHA; Rahmiati, Rahmiati; Rosalina, Linda (Journal of Home Economics and Tourism, 2016)
This study aims to reveal the relationship with Attitude Cosmetics Knowledge Students in Election Cosmetics Skin Care in the Department of Makeup and Beauty Padang State University. This research is a quantitative descriptive correlational. The population in this study were all students of the Department of Education Makeup and Beauty force 2011.2012 and 2013, which amounted to 100 people, while the sample was taken by purposive sampling with stratified sampling amounted to 50 people. Data collection techniques using an objective test items for cosmetics knowledge variable (X) and a questionnaire with Likert scale to measure attitudes in choosing cosmetics (Y). Mechanical analysis of the level of achievement of the respondents with a percentage formula, test requirements analysis using normality test and linearity test while analysis using the Pearson correlation coefficient Product Moment Correlation and continued with the t test for significance analysis of the correlation coefficient and hypothesis testing. Based on the analysis of data obtained an average score of respondents to the attainment of knowledge of cosmetics 82% with high category, the attitude of the students in choosing a facial skin care cosmetics 64% with a bad interpretation. Both variables are weakly associated with a correlation of 0.340. Having the correct considerations in choosing cosmetics is not only based on the wishes and environmental influence but rather the knowledge of good and bad effects in choosing facial skin care cosmetics are used.